Review on various strategies for maximum efficiency of solar panels - Ayoub, Umer; Kaur Channi, Harpreet (International Journal of Engineering and Technology, 2018)
Solar modules are used to convert sunlight directly into electric current. Certain parameters of the module decreases the overall efficiency of the module. These parameters include temperature, soiling, tilt angle. As the temperature increases the output current increases exponentially voltage decreases linearly. To overcome these problems simple,robust,cheap techniques are used to increase overall efficiency of the module.These techniques include MPPT,temperature control, nanowire solar cells and varying tilt angle in summer and winter seasons.Â Â